Pemberdayaan masyarakat dalam meningkatkan nilai tambah hasil perikanan di Kelurahan Pangkalan Lesung Kabupaten Pelalawan - Trisla Warningsih; Kusai Kusai; Lamun Bathara; Zulkarnain Zulkarnain; Isma Mulyani (Unri Conference Series: Community Engagement, 2019)
Pangkalan Lesung Urban Village is located in Pangkalan Lesung District, Pelalawan Regency, Riau Province. Pangkalan Lesung Urban Village has the potential for nature tourism in the form of hot spring baths, the existence of a nature tourism area can improve the economy of the informal sector through the provision of food for tourists who visit. One alternative food that can be done is processed from fishery products. In addition to having processed fishery products that have good nutritional content for health, they also have a high economic value, are used as processed food products and increase family income. The aim of the activity is to empower the community in Pangkalan Lesung Village, Pelalawan to be able to process fishery products into varied and ready-to-serve products. But still healthy for family consumption because it is created with various types of vegetables and fish. The benefit of the activity is that the community of Pangkalan Lesung Village gets the ability and skills in making fish nuggets and meatballs which have high nutritional value, improve the community's economy and can be developed for further business. The method used is a demonstration and practice on how to process fishery products. The target community for this activity is PKK, with 25 members. The results of the evaluation of participants receiving and practising the material processing of fishery products to be used as entrepreneurship on the 17 August 2019 in Pangkalan Lesung Village.